Analisis Pengendalian Persediaan Hangtag Menggunakan Metode Forecasting dan Min-Max Stock pada PT X - Ade Nabila Nurul Kharomah; Irpan Numang (Widyatama University, 2026)
Hangtag inventory is an important component in the product packaging process at PT X. The problem faced by the company is the occurrence of hangtag stockouts due to the lack of accurate inventory planning, which hampers the product delivery process. This study aims to analyze hangtag demand patterns, determine the forecasting method with the best level of accuracy, and apply the Min-Max Stock method to optimize inventory control. The study uses a quantitative approach with historical data on hangtag demand for the period January 2024–March 2026 obtained through observation, interviews, documentation, and company data. The forecasting methods used include Single Moving Average (SMA), Single Exponential Smoothing (SES), and Weighted Moving Average (WMA). Forecasting accuracy is evaluated using MAD, MSE, and MAPE. The results show that the hangtag demand pattern is horizontal (stationary). The Weighted Moving Average (WMA) method for period 3 produces the smallest error rate with a MAPE value of 17.403%, so it is chosen as the basis for implementing the Min-Max Stock method. The calculation yielded a safety stock of 285.86 units, a minimum stock of 1,158 units, a maximum stock of 2,031 units, and a reorder point (ROP) of 873 units. Implementing this method can help companies optimize inventory control and minimize the risk of stockouts and overstocks.